Closing the Global Marine 226Ra Budget Reveals the Biological Pump as a Dominant Removal Flux in the Upper Ocean. Issue 12 (16th June 2022) - Xu, Bochao; Cardenas, M. Bayani; Santos, Isaac R.; Burnett, William C.; Charette, Matthew A.; Rodellas, Valentí; Li, Sanzhong; Lian, Ergang; Yu, Zhigang
Abstract: Radium isotopes are powerful proxies in oceanography and hydrology. Radium mass balance models, including assessments of submarine groundwater discharge (SGD), often overlook particle scavenging (PS) as a pathway for dissolved radium removal from the world ocean. Here, we build a global ocean 226 Ra mass balance model and reevaluate the potential importance of PS. We find that PS is the major 226 Ra sink for the upper ocean, removing about 96% of the total input from various sources. Aside from vertical exchange with the lower ocean, SGD is the largest 226 Ra source into the upper ocean. The biological pump transfers particles to the deep ocean, resulting in a major but often overlooked impact on the global 226 Ra marine budget. Our findings suggest that radium mass balance models should consider PS in systems with high siliceous algae production and export fluxes and long water residence times to prevent underestimation of large‐scale SGD fluxes. Plain Language Summary: Radium is a very powerful tracer for many oceanographic processes. A common assumption in radium investigations is that incorporation into particles plays a negligible role in mass balances. Contrary to this assumption, we found that particle scavenging related to the so‐called "biological pump" is the largest sink for 226 Ra in the global ocean, and that submarine groundwater discharge is the largest terrestrial input. Particle scavenging can be even more important in highly productive coastal systems with long water residence times and high particle burial efficiencies. Particle scavenging, which has been overlooked in many mass balance calculations, may be important for 226 Ra and 228 Ra budgets from local to global scales. Key Points: Particle scavenging is the major 226 Ra sink for the upper ocean, removing about 96% of the total input from various sources Submarine groundwater discharge (SGD) is the largest terrestrial 226 Ra source into the upper ocean, followed by river input and sediment diffusion Particle scavenging can be important in coastal oceans with high primary production and particle burial efficiencies